Suicide in old Norse and Finnish folk stories - Pridmore, S; Ahmadi, J; Majeed, ZA (Australasian Psychiatry, 2011)
Objective: The aim of this study was to examine the folk stories of Norway,Iceland and Finland with a view to discovering accounts of suicide as an escapeoption from intolerable predicaments, and to compare any such accounts withmaterial from Southern Europe.Method: The Poetic Edda (Norway/Iceland) and The Kalevala (Finland)were examined for accounts of suicide, and evidence regarding the infl uence ofthese texts and individual accounts was collected.Results: The Poetic Edda provided one account and The Kalevala three accountsof suicide performed as a means of escaping intolerable situations. Both the PoeticEdda and The Kalevala are in public awareness and have infl uenced the politicsand culture of their respective regions. The individual suicides have been depicted inliterature, music and the visual arts, from the distant past to the present time.Conclusion: Suicide as a means of escape from intolerable predicaments hasbeen public knowledge in these regions for a millennium. This is consistent withfi ndings from Southern Europe and substantiates that intolerable predicamentsmay lead to suicide.